Relationship between the Credit-to-GDP Gap and SystemicBanking Crisis: The Case of Turkey - (:unkn) unknown (My University, 2016)
Çalışmada Türkiye'nin 1960-2013 dönemi yıllık verileri kullanılarak iki aşamalı bir analiz yapılmıştır. Önce Hodrick-Prescott, Band-Pass filtreleri ile Gözlenemeyen Değişken Modeli kullanılarak alternatif kredi açığı hesaplamaları yapılmış ve bunların performansları karşılaştırılmıştır. Ulaşılan bulgular, gözlenemeyen değişken modeline dayanan kredi açığının tahmininin diğerlerine oranla daha başarılı olduğunu göstermiştir. İkinci aşamada, logit kullanılarak ele alınan dönemde Türkiye'de yaşanmış bankacılık krizleri analiz edilmiştir. İkili değişken olarak tanımlanan sistemik krizler ve tüm bankacılık krizleri ayrı ayrı modellenmiş ve bu modellerde açıklayıcı değişken olarak ilk adımda tahmin edilmiş olan kredi açığı dizisi kullanılmıştır. Sonuçlar, kredi açığındaki artışların hem sistemik hem de sistemik olmayan bankacılık krizi meydana gelme olasılığını arttırdığı yönündedir.

In this study, a two-step analysis has been done by using the annual data of Turkey's 1960-2013 periods. First, alternative credit-to-GDP gap calculations were made by using Hodrick-Prescott, Band-Pass filters, and Unobserved Components Model and their performances were compared. Reached findings showed that the credit-to-GDP gap estimations based on the Unobserved Components Model is more successful compared to others. In the second step, banking crisis experienced in Turkey in the studied period has been analysed based on Logit Model. Systemic crises and all banking crises defined as a binary variable were modelled separately. In these models, credit-to-GDP gap estimated in the first step were used as explanatory variable. The results show that the growth in the credit-to-GDP gap increases the probability of occurrence of both systemic and non-systemic banking crises.
and Administrative Sciences
Keywords: Tarih